POTENSI PETANI MILENIAL JAWA BARAT DALAM MENDONGKRAK PEREKONOMIAN NASIONAL MELALUI EKSPOR PRODUK PERKEBUNAN - Yuyun Mulyati; Iin Endah Setyawati; Dudung Ahmad Suganda (Halu Oleo University, 2022)
The purpose of writing is to determine the potential of West Java Millennial Farmers in Boosting the National Economy through the Export of Plantation Products. The method used in this study is a qualitative descriptive approach through observation, interviews, and document studies. Then analyzed using the opinion of Miles, Huberman, and Saldana (2014). The results showed that West Java millennial farmers had a contribution to IDR. 163.335.866.450 (5.89%) of the total export of IDR. 2,768,897,950,950 in boosting the national economy through the export of coffee plantation products, coconut, and their derivatives as well as palm sugar. With current technological developments, the millennial generation can be adaptive to technological developments to be implemented in the agricultural sector, so that the potential of West Java millennial farmers can be developed through technical guidance on cultivation, harvesting, post-harvest, and marketing of plantation products by utilizing digital information technology. In the implementation of the millennial farmer program in West Java, it should be preceded by more intensive socialization by the implementing team and other stakeholders so that it is understood and supported by various levels of society that its implementation is efficient in the use of resources that are factors of production and more effectively achieves the target of increasing income